A Combined Transcriptomic and Proteomic Approach to Reveal the Effect of Mogroside V on OVA-Induced Pulmonary Inflammation in Mice - Dou, Tong; Wang, Juan; Liu, Yisa; Jia, Jiangang; Zhou, Luwei; Liu, Guoxiang; Li, Xiaojuan; Han, Mengjie; Lin, Jiaxun; Huang, Fengxiang; Chen, Xu (Frontiers in Immunology, 2022)
Mogroside V is a bioactive ingredient extracted from the natural food Siraitia grosvenorii which possesses functions that stimulate lung humidification and cough relief activities, but its underlying mechanisms were rarely studied. To estimate its potential protective effect on ovalbumin (OVA)-induced pulmonary inflammation and understand its system-wide mechanism, integrated omics was applied in this study. Mogroside V effectively reduced the levels of IgE, TNF-α, and IL-5 in OVA-induced mice. The results of RNA-seq and data-independent acquisition proteomics approach revealed that 944 genes and 341 proteins were differentially expressed in the normal control group (NC) and ovalbumin-induced control group (OC) and 449 genes and 259 proteins were differentially expressed between the OC and the group treated with 50 mg/kg mogroside V (MV). After a combined analysis of the transcriptome and the proteome, 93 major pathways were screened, and we discovered that mogroside V exerts an anti-inflammation effect in the lung via NF-κB and JAK-STAT, both of which are among the signaling pathways mentioned above. In addition, we found that the key regulatory molecules (Igha, Ighg1, NF-κB, Jak1, and Stat1) in the two pathways were activated in inflammation and inhibited by mogroside V. Thus, mogroside V may be the main bioactivity component in S. grosvenorii that exerts lung humidification and cough relief effects.